Diffusion Tensor Imaging in Idiopathic REM Sleep Behavior Disorder Reveals Microstructural Changes in the Brainstem, Substantia Nigra, Olfactory Region, and Other Brain Regions - Unger, Marcus M.; Belke, Marcus; Menzler, Katja; Heverhagen, Johannes T.; Keil, Boris; Stiasny-Kolster, Karin; Rosenow, Felix; Diederich, Nico J.; Mayer, Geert; Möller, Jens C.; Oertel, Wolfgang H.; Knake, Susanne (Sleep (New York, N.Y.), 2010)
Idiopathic rapid eye movement sleep behavior disorder (iRBD)--a parasomnia characterized by dream enactments--is a risk marker for the development of Parkinson disease (PD) and other alpha-synucleinopathies. The pathophysiology of iRBD is likely due to dysfunction of brainstem nuclei that regulate REM sleep. Diffusion tensor imaging (DTI) is a method for studying microstructural brain tissue integrity in vivo. We investigated whether DTI detects microstructural abnormalities in the brain of patients with iRBD--compared with age-matched control subjects--as an in vivo potential indicator for changes related to "preclinical (premotor)" neuropathology in PD. N/A. Patients with iRBD (n = 12) and age-matched healthy control subjects (n = 12) were studied. At a 1.5T MRI maschine, whole-head DTI scans of fractional anisotropy, axial diffusivity (a potential marker of neuronal loss), and radial diffusivity (a potential marker of glial pathology) were analyzed using track-based spatial statistics, and 2 types of group analysis tools (FreeSurfer and FSL). We found significant microstructural changes in the white matter of the brainstem (P < 0.0001), the right substantia nigra, the olfactory region, the left temporal lobe, the fornix, the internal capsule, the corona radiata, and the right visual stream of the patients with iRBD. Changes were identified in regions known to be involved in REM-sleep regulation and/or to exhibit neurodegenerative pathology in iRBD and/or early PD. The study findings suggest that iRBD-related microstructural abnormalities can be detected in vivo with DTI, a widely available MRI technique.